Inhibition Test of Uncaria cordata (Lour.) Merr Extract Against Pathogenic Bacteria of Freshwater Fish In Vitro - Maryani, Maryani; Rozik, Mohamad; Madiyawati, Milad; Yuli, Yuli (Journal of Fish Health, 2024)
Uncaria is a genus of plants that have medicinal properties and chemical content. Uncaria cordata (Lour.) Merr is a herbal plant that is still rarely known for its efficacy in herbal medicinal ingredients. Uncaria cordata (Lour.) Merr it self contains metabolic compounds in the form of flavonoid, phenolic, steroid, saponin, terpenoid and alkonoid. This study aims to test the effectiveness of Uncaria cordata (Lour.) Merr as an antimicrobial on Aeromonas hydrophila, Pseudomonas sp. and Edwardsiella ect.) Merr as an antimicrobial on Aeromonas hydrophila, Pseudomonas sp. and Edwardsiella ictaluri bacteria and the type of bacteria that are more effective in using Uncaria cordata (Lour.) Merr in inhibiting the proliferation of disease-causing bacteria in cultured fish. The results showed that Uncaria cordata (Lour.) Merr, was able to inhibit the proliferation of bacteria Aeromonas hydrophila, Pseudomonas sp. and Edwardsiella ictaluri with an average diameter of the inhibition zone of Aeromonas hydrophila bacteria at a concentration of 100% forming an inhibition zone of 21.7 mm with a very strong inhibition zone category, in the bacteria Pseudomonas sp. at 100% concentration formed an inhibition zone of 21 mm with a very strong inhibition zone category, and in Edwardsiella ictaluri bacteria at 100% concentration formed an inhibition zone of 21.3 mm with a very strong inhibition zone category. The 100% concentration of Uncaria cordata (Lour.) Merr is the most effective concentration to inhibit bacterial proliferation.